Resilience to Nested Crises: The Effects of the Beirut Explosion on COVID-19 Safety Protocol Adherence During Humanitarian Assistance to Refugees - Nawyn, Stephanie; Karaoğlu, Ezgi; Gasteyer, Stephen; Mansour, Rania; Ghassani, Ali; Marquart-Pyatt, Sandra (Frontiers in Public Health, 2022)
To provide services safely to refugees during the COVID-19 pandemic, humanitarian non-governmental organizations (NGOs) have instituted public health safety protocols to mitigate the risk of spreading the SARS-CoV-2 virus. However, it can be difficult for people to adhere to protocols under the best of circumstances, and in situations of nested crises, in which one crisis contributes to a cascade of additional crises, adherence can further deterioriate. Such a nested crises situation occurred to Beirut, Lebanon, when a massive explosion in the city injured or killed thousands and destroyed essential infrastructure. Using data from a study on COVID-19 safety protocol adherence during refugee humanitarian assistance in Lebanon, Jordan, and Turkey, we conduct a cross-country comparison to determine whether the nested crises in Beirut led to a deterioration of protocol adherence–the “fragile rationalism” theory–or whether adherence remained robust–the “collective resilience” theory (Reicher and Bauld 2021. We found greater evidence for collective resilience, and from those findings make public health recommendations for service provision occurring in disaster areas.